Job Security Without Equality: The Family and Medical Leave Act of 1993 - Joanna L. Grossman (Washington University Journal of Law & Policy, 2004)
This Essay reevaluates the passage and implementation of the FMLA against the egalitarian ideal described by the Supreme Court in Hibbs. Part I examines the Hibbs opinion, the Court’s conclusion that states can be sued for money damages in federal court for violating the family care provisions of the FMLA, and the vision of the Act’s contribution to equality that dictated that holding. Part II examines the data available to both legislators and advocates during the process of constructing and enacting family leave legislation, with a particular focus on existing knowledge about patterns of paternal leave-taking. Part III begins the process of reevaluation, looking first at the legislative history of the FMLA and the advocacy that led to its original and repeated introductions into both houses of Congress. This part identifies a central assumption, shared by both opponents and proponents of the final Act and its predecessor bills, that federally mandated leave would primarily accommodate the leave-taking needs of mothers. Part IV examines the FMLA’s impact on leave policies and leave-taking, noting the replication of prior gendered, leave-taking patterns. Finally, Part V launches a critique of the FMLA from the standpoint of anti-subordination theory. Through that lens, the FMLA’s ability to enhance equality for women seems quite constrained.
Keywords: Parental leave; Sex discrimination in employment; Parenting